DEVELOPMENT OF AUTOMATIC TORQUE BOND TEST - Muslich Hartadi Sutanto (Jurnal Transportasi, 2011)
Proper bonding between adjacent pavement layers is very important to ensure good pavement performance. Manual torque bond test is known to be one of the tests to determine mechanical properties of bond between adjacent pavement layers. However, the test has several drawbacks that may affect the accuracy of results. This paper is focused on the development a mechanically controlled automatic torque bond test in order to eradicate the drawbacks associated with the manual torque bond test. A trial test and calibration of the newlydeveloped apparatus was performed to ensure the accuracy of results. The nominal loading rate of the manual torque bond test performed at 600Nm/min was found to be lower than the target loading rate, leading to a lower measured shear strength compared to that of the automatic torque test. It was also found that the appearance of lateral shear would not significantly affect the shear strength.Keywords: bond test, torque, shear, loading rate.